CHOOSING VITAMINS - O.V. Yozefovich; A.A. Ruleva; S.M. Kharit; N.N. Murav'yova ("Paediatrician" Publishers LLC, 2010)
The deficiency of vitamins is one of the main reasons of health worsening. The lack or the absence of vitamins results in metabolic disorders, decrease of physical and intellectual development, and quick fatigability of organism. Besides the regular inclusion of food, fortified with vitamins, the reliable source of vitamins and minerals are multivitamin preparations and vitamins and minerals complexes for the prophylactic use. At the time of administration vitamins, the daily need, the presence of micronutrients deficiency, and compatibility and balance of vitamins and minerals complexes must be taken into account. Key words: children, vitamins deficiency. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):172-176)